PENGARUH TARIF DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RSUD RAA SOEWONDO PATI - Kusuma, Edi Wijaya; Suryoko, Sri; Budiatmo, Agung (Jurnal Ilmu Administrasi Bisnis, 2014)
Decrease the number of hospitalized patients suspected to be caused by the increase in service rates hospitals Soewondo Starch RAA. Aside from the issue of health care levy rate increase is also due to the performance indicators of hospitals RAA. Starch Soewondo weakened. So it is necessary to do research on "The Effect of Rates and Service Quality Customer Satisfaction on RSUD RAA. Soewondo Pati. Â From the research it can be seen that the rates given by RSUD RAA Soewondo Pati can be perceived appropriate. Hospital Service Quality RSUD RAA Soewondo Pati perceived good. Costumer Satisfaction Patient Hospital Pati RAA Soewondo classified satisfied. Variable rates have a positive and significant effection customer satisfaction variable. Variable Quality of Service has a positive and significant impact on consumer satisfaction. Variable rates, and quality of service have a significant influence on consumer satisfaction, so the hypothesis is accepted. Â Suggestions may be submitted by the author to the RSUD RAA Soewondo Pati are RSUD RAASoewondo Pati need to provide better service. It should be repaired speed of the accepted the patients that are considered less by some patients. And also more attention to patients personally, will cause the patient to be more comfortable. And Some Patients RSUD RAA Soewondo Pati, will feel more satisfied if the speed of the accepted the patients repaired and also incresing more attention to patients personally.